1980
DOI: 10.1111/j.1365-2621.1980.tb04083.x
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella AND OTHER BACTERIA ON ALFALFA AND BEAN SPROUTS AT THE RETAIL LEVEL

Abstract: Sprouts from nine producers were sampled from retail outlets and the microbial flora identified. Total aerobic plate counts were 108 cells/g; psychrotrophic counts were 107 cells/g; lactobacilli and fecal streptococci counts were low. Total coliforms and confirmed Klebsiella counts were each 106 cells/g. Fecal coliforms appeared to be part of the normal flora of sprouts (1,100 to 240,000 MPN per 100g). These were primarily K. pneumoniae. Sixty‐four percent of selected K. pneumoniae isolates were fecal colifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 23 publications
3
30
1
Order By: Relevance
“…[5] In the present outbreak, the vehicle of infection was contaminated beansprouts and the source of infection contaminated mung bean seeds. The degree of contamination was reflected in the frequent finding of E. coli on routine sampling of beansprouts.…”
Section: Discussionmentioning
confidence: 78%
“…[5] In the present outbreak, the vehicle of infection was contaminated beansprouts and the source of infection contaminated mung bean seeds. The degree of contamination was reflected in the frequent finding of E. coli on routine sampling of beansprouts.…”
Section: Discussionmentioning
confidence: 78%
“…Such high levels of microorganisms on bean sprouts have been recognised for many years. In fact, bean sprouts from retail outlets were revealed to give high total plate counts of 8e9 log cfu/g (Patterson & Woodburn, 1980). The study conducted in Philippines showed that the total plate count of the mung bean sprouts ranged from 4.5 to 11.4 log cfu/g (Gabriel et al, 2007).…”
Section: Microbiological Quality Of Fresh Fruits and Vegetablesmentioning
confidence: 96%
“…The high microbial level perse is not necessarily of public health concern, rather, the presence and growth of pathogens in the produce (National Advisory Committee on Microbiological Criteria for Foods, 1999). Fresh sprouts typically have total plate counts as high as 10 8 -10 9 CFU/g (Patterson & Woodburn, 1980;Viswanathan & Kaur, 2001;Gabriel et al, 2007) due to the intrinsic microflora of the seeds and the favorable environment in which they are grown (Buck et al, 2003). However, poor hygienic practices of producers and retailers and unsanitary sprouting conditions could also contribute to the high level of microbiological populations in sprouts (Gabriel et al, 2007).…”
Section: Microbiological Status Of Sprouts and Seedsmentioning
confidence: 97%